(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The article is devoted to the organization of independent work of students enrolled in the direction of teacher training based on web quests. An example of an educational web quest for the 3rd year is the “Inclusive School”. One of the leading directions of development of the system of higher pedagogical education is the strengthening of the practice-oriented orientation of the study of disciplines, including the educational cycle. This concerns not only an increase in the share of active and interactive methods in teaching, an increased attention to organizing and conducting internships in educational institutions, but also a change in the approach to organizing independent work of bachelor students. Much attention is increasingly given to increasing the level of information and communication competence of future teachers (electronic libraries and educational Internet portals are the main source of educational information for modern students), it is advisable to use information and communication technologies as an organizational and substantive basis for independent work. This approach to the organization of independent work involves the development of tasks by teachers using Internet technologies, which, depending on the type of task, can be performed online or offline. Tasks for independent work can be directed to an independent search in the network with the subsequent processing of information about a specific problem; on the organization of interaction in the network; create web pages; conduct educational research, social or educational projects. The forms for presenting the results may also vary: text documents (with hyperlinks), databases of multimedia presentations, web pages, web quests. Particular attention, in our opinion, should be paid to teaching real web quests. A web quest is considered as an activity-oriented didactic model that provides for students' independent search work on the Internet. As a form of organizing independent work, a web quest has several advantages, including: increased student motivation; activation of individual or group activities; more efficiently use the understanding of the time allotted for independent work of students; the ability to not only integrate different types of assignments and forms of providing results, but also to vary the level of difficulty of the task for independent work, the duration of implementation, the number of performers.